Prevalence of risk factors for human immunodeficiency virus among sexually active women in Rwanda: a nationwide survey - Joseph Kawuki; Lilian Nuwabaine; Angella Namulema; John Baptist Asiimwe; Quraish Sserwanja; Ghislaine Gatasi; Elorm Donkor (BMC, 2023)
Abstract Background The Human Immunodeficiency Virus (HIV) remains a global health burden, and despite the advancements in antiretroviral therapy and various strategies employed to curb HIV infections, the incidence of HIV remains disproportionately high among women. Therefore, this study aimed to determine the prevalence of the risk factors for the acquisition of HIV among sexually active women in Rwanda. Methods Secondary data from the 2020 Rwanda Demographic Health Survey, comprising 10,684 sexually active women, was used. Multistage stratified sampling was employed to select the study participants. Multivariable logistic regression was conducted to determine the associated risk factors using the SPSS (version 25). Results Of the 10,684 sexually active women, 28.7% (95% confidence interval (CI): 27.5-29.4) had at least one risk factor for HIV acquisition. Having no education (AOR = 3.65, 95%CI: 2.16-6.16), being unmarried (AOR = 4.50, 95%CI: 2.47-8.21), being from female-headed households (AOR = 1.75, 95%CI: 1.42-2.15), not having health insurance (AOR = 1.34, 95%CI: 1.09-1.65), no HIV test history (AOR = 1.44, 95%CI: 1.01-2.08), being from the poorest wealth quintile (AOR = 1.61, 95%CI: 1.14-2.27) and lack of exposure to mass media (AOR = 1.30, 95%CI: 1.07-1.58) were associated with higher odds of exposure to at least one HIV acquisition risk factor. In contrast, age groups of 25-34 (AOR = 0.56, 95%CI: 0.44-0.71) and 35-44 years (AOR = 0.62, 95%CI: 0.48-0.80), rural residence (AOR = 0.63, 95%CI: 0.49-0.81) and being from the western region (AOR = 0.67, 95%CI: 0.48-0.94) were associated with less odds of exposure to at least one HIV acquisition risk factor. Conclusion More than a quarter of sexually active women in Rwanda had exposure to at least one risk factor for HIV acquisition. There is a need to maximize the use of mass media in disseminating HIV prevention and behavioral change messages. Engagement of religious leaders and promotion of HIV testing, especially among the never-testers, may be vital strategies in successful HIV prevention programs.